PHOTO-REDUCTION KINETICS OF MnO2 IN AQUATIC ENVIRONMENTS CONTAINING HUMIC ACIDS - Narsito Narsito; Sri Juari Santosa; Setya Lastuti (Indonesian Journal of Chemistry, 2008)
The kinetics of photo-reduction of manganese(IV) oxide, MnO2 in aqueous medium, in the presence of humic acid has been investigated, including the possibility for the involvement of such radicals in the reduction. Results showed that in aqueous medium, the efficiency of the photo-reduction of MnO2 producing a soluble ionic Mn(II) was governed strongly by an internal electron transfer within an intermediate of HA-MnO2 anion complex, resulted in the chemical adsorption of humic acid on MnO2 surface. It was observed that under solar radiation and atmosphere containing oxygen, the rate of MnO2 reduction increased considerably, by factors of about 46 and 2 respectively. Moreover, there was evidence that some radicals certainly played a role in the photo-reduction of MnO2, since radical scavenger addition significantly decreased the reduction efficiency of MnO2. In the present of an excess of propanol-2, however, which was expected to remove all OH radicals present, only about 60 % decrease in reduction efficiency were observed, suggesting that radicals other than OH radical are involved in the reduction of MnO2. It was observed further that the presence of iron(III) in MnO2 up to 1 % (w/w) did not alter the reduction efficiency of MnO2.